Synthesis and characterization of aromatic polyazomethines bearing pendant pentadecyl chains - More, Arvind S.; Sane, Prakash S.; Patil, Anandrao S.; Wadgaonkar, Prakash P. (Polymer Degradation and Stability, 2010)
Aromatic diamine monomer viz., 4-(4'-aminophenoxy)-2-pentadecylbenzenamine containing pendant pentadecyl chain was synthesized starting from cashew nut shell liquid - a renewable resource material and was characterized by FTIR, (1)H and (13)C NMR spectroscopy. A series of new (co) polyazomethines containing pendant pentadecyl chains and flexibilizing ether linkages was synthesized by polycondensation of 4-(4'-aminophenoxy)-2-pentadecyl benzenamine with commercially available aromatic dialdehydes viz., terephthaldehyde (TPA), isophthaldehyde (IPA) and varying mixture of TPA and IPA. Inherent viscosities and number average molecular weights of (co) polyazomethines were in the range 0.50-0.70 dL/g and 10,490-40-800 (GPC, polystyrene standard), respectively indicating formation of medium to reasonably high molecular weight polymers. (Co) polyazomethines containing pendant pentadecyl chains were found to be soluble in common organic solvents such as chloroform, dichloromethane, tetrahydrofuran, pyridine, m-cresol and could be cast into transparent and stretchable films from their solution in chloroform. (Co) polyazomethines were essentially amorphous in nature and the formation of loosely-developed layered structure was observed arising from the packing of pendant pentadecyl chains. Polyazomethines exhibited glass transition temperatures (T(g)) in the range 21-48 degrees C. The observed depression of glass transition temperature could be ascribed to the ``internal plasticization'' effect of pentadecyl chains. The temperature at 10% wt loss (T(10)), determined from TGA in nitrogen atmosphere of polyazomethines were in the range 434-441 degrees C indicating their good thermal stability. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Cashew nut shell liquid; CNSL; pentadecyl; polyazomethines; renewable; Side-chain; solubility

Synthesis and characterization of polyamides containing pendant pentadecyl chains - More, Arvind S.; Pasale, Sharad K.; Wadgaonkar, Prakash P. (European Polymer Journal, 2010)
A new aromatic diacid monomer viz., 4-(4'-carboxyphenoxy)-2-pentadecylbenzoic acid was synthesized starting from cardanol and was characterized by FTIR, (1)H- and (13)C NMR spectroscopy. A series of new aromatic polyamides containing ether linkages and pendant pentadecyl chains was prepared by phosphorylation polycondensation of 4-(4'-carboxyphenoxy)-2-pentadecylbenzoic acid with five commercially available aromatic diamines viz., 1,4-phenylenediamine, 4,4'-oxydianiline, 4,4'-methylenedianiline, 1,3-phenylenediamine, and 4,4'-(hexafluoroisopropylidene)dianiline. Inherent viscosities of the polyamides were in the range 0.45-0.66 dL/g in N,N-dimethylacetamide at 30 +/- 0.1 degrees C. The introduction of ether linkages and pendant pentadecyl chains into polyamides led to an enhanced solubility in N,N-dimethylacetamide and 1-methyl-2-pyrrolidinone at room temperature or upon heating. The polyamides could be solution-cast into tough, flexible and transparent films from their N,N-dimethylacetamide solution. Wide angle X-ray diffraction patterns exhibited broad halo indicating that the polymers were essentially amorphous in nature. X-Ray diffractograms also displayed a diffuse to sharp reflection in the small-angle region (20 = similar to 2-5 degrees) for the polyamides characteristics of formation of loosely to well-developed layered structure arising from packing of flexible pentadecyl chains. The glass transition temperature observed for the polyamides was in range 139-189 degrees C. The temperature at 10% weight loss (T(10)), determined by TGA in nitrogen atmosphere, of the polyamides was in the range 425-453 degrees C indicating their good thermal stability. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: alkyl side-chain; Cardanol; Cashew nut shell liquid; Pentadecyl chains; polyamides

Synthesis and characterization of polyesters based on 1,1,1-[bis(4-hydroxyphenyl)-4 `-pentadecylphenyl]ethane - More, Arvind S.; Naik, Parimal V.; Kumbhar, Kishor P.; Wadgaonkar, Prakash P. (Polymer International, 2010)
Aromatic polyesters are of considerable interest because of their excellent mechanical properties, chemical resistance and thermal stability. However, most aromatic polyesters are difficult to process due to their high glass transition temperatures coupled with their insolubility in common organic solvents. The present article describes a series of organosoluble polyesters and copolyesters based on 1,1,1-[bis(4-hydroxyphenyl)-4'-pentadecylphenyl]ethane. A series of new aromatic polyesters containing pendant pentadecyl chains was synthesized by interfacial polycondensation of 1,1,1-[bis(4-hydroxyphenyl)-4'-pentadecylphenyl]ethane with terephthalic acid chloride (TPC), isophthalic acid chloride (IPC) and a mixture of TPC and IPC. A series of copolyesters was synthesized from 4,4'-isopropylidenediphenol with TPC by incorporating 1,1,1-[bis(4-hydroxyphenyl)-4'-pentadecylphenyl]ethane as a comonomer. Inherent viscosities of the polyesters and copolyesters were in the range 0.72-1.65 dL g(-1) and number-average molecular weights were in the range 18 170-87 220. The polyesters and copolyesters containing pendant pentadecyl chains dissolved readily in organic solvents such as chloroform, dichloromethane, pyridine and m-cresol and could be cast into transparent, flexible and apparently tough films. Wide-angle X-ray diffraction data revealed the amorphous nature of the polyesters and copolyesters. The formation of loosely developed layered structure was observed due to the packing of pendant pentadecyl chains. The temperature at 10% weight loss, determined using thermogravimetric analysis in nitrogen atmosphere, of the polyesters and copolyesters containing pendant pentadecyl chains was in the range 400-460 degrees C. The polyesters and copolyesters exhibited glass transition temperatures in the range 63-82 degrees C and 177-183 degrees C, respectively. (C) 2010 Society of Chemical Industry
Keywords: cashew nutshell liquid; CNSL; pentadecyl; polyesters; renewable

Synthesis and characterization of organo-soluble poly(ether ether ketone)s and poly(ether ether ketone ketone)s containing pendant pentadecyl chains - More, Arvind S.; Pasale, Sharad K.; Honkhambe, Pandurang N.; Wadgaonkar, Prakash P. (Journal of Applied Polymer Science, 2011)
Poly(ether ether ketone)s and poly(ether ether ketone ketone) s containing pendant pentadecyl chains were synthesized by polycondensation of each of the two bisphenol monomers viz, 1,1,1-[bis(4-hydroxyphenyl)-4'-pentadecylphenyl] ethane and 1,1-bis(4-hydroxyphenyl)-3-pentadecyl cyclohexane with activated aromatic dihalides namely, 4,4'-difluorobenzophenone, and 1,3-bis(4-fluorobenzoyl) benzene in a solvent mixture of N,N-dimethylacetamide and toluene, in the presence of anhydrous potassium carbonate. Polymers were isolated as white fibrous materials with inherent viscosities and number average molecular weights in the range 0.70-1.27 dL g(-1) and 76,620-1,36,720, respectively. Poly(ether ether ketone) s and poly(ether ether ketone ketone) s were found to be soluble at room temperature in organic solvents such as chloroform, dichloromethane, tetrahydrofuran, and pyridine and could be cast into tough, transparent, and flexible films from their solutions in chloroform. Wide angle X-ray diffraction patterns exhibited a broad halo at around 2 theta = similar to 19 degrees indicating that the polymers containing pentadecyl chains were amorphous in nature. In the small-angle region, diffuse reflections of a typically layered structures resulting from the packing of pentadecyl side chains were observed. The temperature at 10% weight loss, obtained from TG curves, for poly(ether ether ketone) s and poly(ether ether ketone ketone) s were in the range 416-459 degrees C, indicating their good thermal stability. A substantial drop in glass transition temperatures (68-78 degrees C) was observed for poly(ether ether ketone) s and poly(ether ether ketone ketone) s due to ``internal plasticization'' effect of flexible pendant pentadecyl chains. (C) 2011 Wiley Periodicals, Inc. J Appl Polym Sci 121: 3689-3695, 2011
Keywords: alkyl side-chain; Cashew nut shell liquid; CNSL; pentadecyl; poly(arylene ether)s; poly(ether ketone)s; polyethers; renewable

Step-growth polymers from cashew nut shell liquid (CNSL)-based aromatic difunctional monomers - Chatterjee, Deepshikha; Sadavarte, Nilakshi V.; Shingte, Rahul D.; More, Arvind S.; Tawade, Bhausaheb V.; Kulkarni, Arun D.; Ichake, Amol B.; Avadhani, C. V.; Wadgaonkar, Prakash P. (Cashew Nut Shell Liquid, 2017)
Cashew nut shell liquid (CNSL) is an attractive renewable resource material which is available in abundance (44,50,000 tonnes worldwide and 7,53,000 tonnes in India in 2013) at low cost (around 0.27 $/kg in 2015) and is mainly composed of anacardic acid, cardanol, cardol and 2-methyl cardol. Cardanol is obtained as a major product during hot oil extraction or roasting process of CNSL. Cardanol possesses interesting structural features. The aromatic ring of cardanol can undergo electrophilic substitution reactions; the unsaturated side chain can undergo epoxidation, hydrogenation, metathesis, etc., while the phenolic hydroxyl group can undergo various reactions such as esterification and alkylation. Such opportunities of chemical modifications offered by cardanol have been extensively explored to synthesise a range of interesting aromatic difunctional monomers that have subsequently been utilised to prepare a host of step-growth polymers. Summarised herein are research efforts that have contributed towards the synthesis of step-growth polymers based on aromatic difunctional monomers derived from cardanol. The properties of high-performance polymers, with a particular focus on processability and thermal characteristics, are highlighted.